Surgeons and the 'God complex'. Issue 3 (May 2017) - Kirby, Roger
Abstract : The recent publicity surrounding the prosecution and conviction of breast cancer surgeon Ian Paterson risks seriously undermining trust in surgery and in surgeons, especially in relation to his reported arrogance and supposed 'God complex'. Sadly, he is not the first surgeon to be accused of these unfortunate characteristics – nor will he be the last…